HEAD MANAGEMENT SCHOOLS IN IMPLEMENTING INCLUSIVE SCHOOLS IN STATE ELEMENTARY SCHOOLS OF GUGUS III, DEWANTARA DISTRICT REGENCY NORTH ACEH - Zahara; Sonny Muhammad Ikhsan Mangkuwinata; Iskandar Idris (RADJA PUBLIKA, 2026)
This study aims to describe the Principal's Management in Implementing Inclusive Schools in State Elementary Schools Cluster III, Dewantara District, West Java Regency. North Aceh and the supporting and inhibiting factors of Principal Management in Implementing Inclusive Schools in State Elementary Schools Cluster III, Dewantara District, Aceh North Aceh. This research is a descriptive study using qualitative methods with a phenomenon approach or direct observation and interaction in the field. The subjects in This research is the principal and several teachers who teach at inclusive class. Technique collection data using interviews, observations, and also documentation studies. Data presentation analysis techniques use data reduction, data presentation, and documentation. data And withdrawal conclusion to participants in field without the existence of engineering. Meanwhile, the data validity test uses the criteria of degree of trust, transferability, dependence And certainty participants as source person. Results research shows that (1) Principal Management in Implementing Inclusive Schools in State Elementary Schools Cluster III, District Dewantara Regency Aceh North Already Can it is said Good. Can seen from the management process carried out with POAC elements, namely planning, organizing, implementing and evaluating. (2) supporting factors, namely laws that regulate about school inclusive, and factor inhibitors, namely unavailability or inadequate supporting facilities and infrastructure, support from the local community and accompanying teachers who are not graduates of inclusive education for students with special needs.